2013
DOI: 10.1111/j.2047-2927.2013.00136.x
|View full text |Cite
|
Sign up to set email alerts
|

The association between TNF-α and erectile dysfunction complaints

Abstract: SUMMARYInflammatory markers like tumour necrosis factor-alpha (TNF-a) have been related to erectile dysfunction (ED) and may interact with other cardiovascular risk factors such as obstructive sleep apnoea syndrome (OSAS). The aim of this study was to examine the inflammatory, metabolic and hormonal profile of men with or without ED complaints and/or OSAS recruited through the Epidemiologic Sleep Study (EPISONO). A sample of 363 men completed sexual questionnaires for ED and had physical and blood examinations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…Blood levels of TNFa, along with other pro-inflammatory (IL-6, IL-1b) and prothrombotic factors, were significantly increased in ED patients and negatively related to sexual performance (Vlachopoulos et al, 2006). Similar results were also found in patients with type 2 diabetes mellitus (Araña Rosaínz Mde et al, 2011) and in patients with obstructive sleep apnea syndrome (Matos et al, 2013). Animal models involving genetic manipulation of TNFa, have shown peculiar alterations of erectile function.…”
Section: Discussionsupporting
confidence: 56%
“…Blood levels of TNFa, along with other pro-inflammatory (IL-6, IL-1b) and prothrombotic factors, were significantly increased in ED patients and negatively related to sexual performance (Vlachopoulos et al, 2006). Similar results were also found in patients with type 2 diabetes mellitus (Araña Rosaínz Mde et al, 2011) and in patients with obstructive sleep apnea syndrome (Matos et al, 2013). Animal models involving genetic manipulation of TNFa, have shown peculiar alterations of erectile function.…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, other investigators reported that ED was associated with increased levels of TNF-a and CRP, which increased progressively with the severity of penile vascular disease, supporting the role of these markers in the pathophysiology of ED [22, 23]. Furthermore, recently, Matos et al showed that there was an association between TNF-a levels and ED complaints in men independent of OSAHS [24]. It is worth noting that, in a recent study, reduced levels of adiponectin, an anti-inflammatory cytokine that attenuates endothelial cell adhesion molecules, and the levels of inflammatory cytokines, such as TNF-a, IL-8, and IL-6, were observed in patients with ED [25].…”
Section: Discussionmentioning
confidence: 90%
“…TNF‐α contributes to the dysregulation of insulin modulation of endothelin‐1‐mediated vasoconstriction and NO‐mediated vasodilation. It is likely that TNF‐α may reduce NO release and its metabolites, which, in turn, affects penile erection [101]. It has been suggested that increased expression of TNF‐α in obesity and subsequent reduced expression of adiponectin plays a significant role in development of the MetS [102].…”
Section: Inflammationmentioning
confidence: 99%